Barriers to Effective Pain Management in Postoperative Patients: Perspectives of Nurses in Pakistan - Perveen, Rehana; Anwar, Saima; Kainat, Sajjal; Javed, Abia; Mahmood, Iram (Biological and Clinical Sciences Research Journal, 2025)
Effective pain management is a cornerstone of quality postoperative care. However, in Pakistan, nurses face multiple barriers, including staffing shortages, lack of resources, inadequate training, and cultural influences that hinder optimal patient outcomes. Understanding these barriers is essential for developing targeted interventions. Objective: To identify and analyze the barriers perceived by nurses in providing effective postoperative pain management in a tertiary care hospital in Pakistan. Methods: This descriptive cross-sectional study was conducted from July to December 2024 in a tertiary care hospital. A total of 99 registered nurses working in surgical and postoperative wards were recruited through purposive sampling. Data were collected using a structured, pre-validated questionnaire consisting of demographic details and a 5-point Likert scale assessing institutional, professional, and patient-related barriers. Descriptive statistics were used for demographic variables, and Chi-square tests assessed associations between demographics and perceived barriers. A p-value of <0.05 was considered statistically significant. Results: The majority of participants were female (83.8%), with a mean age of 29.7 ± 5.6 years. Most nurses held a diploma in nursing (59.6%) and had 1–5 years of experience (53.5%). The most frequently reported barriers included time constraints/work overload (48.5%), inadequate staffing (46.5%), lack of pain assessment tools (42.4%), and poor communication with physicians (41.4%). Nurses with less than five years of experience perceived inadequate staffing (p = 0.043) and limited pharmacological knowledge (p = 0.009) as significantly greater barriers compared to more experienced nurses. Conclusion: Nurses in Pakistan encounter multiple barriers in managing postoperative pain, primarily related to staffing, workload, inadequate tools, and limited pharmacological knowledge. Tailored educational programs, supportive institutional policies, and improved inter-professional collaboration are vital to enhance pain management and improve patient recovery outcomes.